Examining the Effects of Couples’ Real-Time Stress and Coping Processes on Interaction Quality: Language Use as a Mediator - Lau, Kevin K. H.; Randall, Ashley K.; Duran, Nicholas D.; Tao, Chun (Frontiers in Psychology, 2019)
Stress in romantic relationships is an all-too-common phenomenon that has detrimental effects on relationship well-being. Specifically, stress can lead to negative interactions between partners and ultimately decrease relationship functioning. The systemic-transactional model of dyadic coping posits that by effectively communicating stress and coping with one another, couples can mitigate the deleterious effects of stress. Specifically, partners can engage in positive dyadic coping by helping each other cope with his/her respective stress, which may foster couples’ sense of “we-ness,” strengthen their emotional connection, and facilitate their understanding of each other’s stressful experiences. However, these associations have not yet been examined during partners’ interactions about stress. When assessing dyadic coping, a particular aspect of interest is partners’ language use (i.e., pronouns, emotion words, cognition words) as it may reflect the types of support they communicate to one another. Using real-time interaction data from 41 heterosexual couples, this study examined how couples’ stress and coping processes affect perceived interaction quality following discussions of stress. Specifically, language use (i.e., pronouns, emotion words, cognition words) was assessed as mediator in the association between observed stress communication and perceived interaction quality. Overall, results supported our hypotheses; when one partner communicated stress, the other partner responded with language use indicative of different types of dyadic coping (i.e., more you-talk and use of emotion words, less we-talk, I-talk, and use of cognition words), which were in turn associated with interaction quality in mixed directions. Implications of these findings for romantic couples are discussed.